Effect of Consumer Ethnocentrism and Perceived Quality of Product on Buying Behavior of Domestic and Foreign Food Products: A Case Study in Pekanbaru, Riau, Indonesia - Rahmawati, Nanda Amalia; Muflikhati, Istiqlaliah (Journal of Consumer Sciences, 2016)
Due to the entry of foreign food products, not only domestic food products does Indonesia provide to the consumers, but also foreign food products. This study aimed to analyze the effects of consumer ethnocentrism and perceived quality product on the buying behavior of domestic and foreign food products. This study used cross-sectional design study involving data from 100 consumers of Bawah Market Pekanbaru who were chosen by convenience sampling technique. The results showed that the respondents had a medium level of consumer ethnocentrism. They perceived the quality of domestic food products  higher than that of foreign food products. The results of the multinomial logistic regression test showed that ethnocentrism and perceived quality of domestic food products had a significant negative effect on the food product purchases. Specifically, consumers who had a higher level of ethnocentrism were less likely to purchase foreign food products. Meanwhile, consumers who had a higher level of perceived quality of domestic food product were less likely to purchase the mixture of domestic and foreign food products.Keywords: ethnocentrism, buying behavior, perceived quality of the product Masuknya produk makanan luar negeri ke Indonesia menyediakan konsumen alternatif bagi produk dalam negeri. Penelitian ini bertujuan untuk menganalisis pengaruh etnosentrisme konsumen dan persepsi kualitas produk terhadap perilaku pembelian produk makanan dalam dan luar negeri. Penelitian ini menggunakan desain cross sectional study dengan data yang diperoleh dari 100 orang konsumen di Pasar Bawah Pekanbaru yang dipilih menggunakan convenience sampling technique. Hasil penelitian menunjukkan etnosentrisme konsumen pada umumnya mencapai tahap sedang. Persepsi kualitas produk makanan dalam negeri lebih tinggi daripada persepsi kualitas produk makanan luar negeri. Hasil uji regresi logistik multinomial menunjukkan bahwa etnosentrisme dan persepsi kualitas produk dalam negeri memengaruhi pembelian produk makanan secara signifikan dan negatif. Konsumen yang memiliki etnosentrisme yang tinggi kurang cenderung untuk membeli produk luar negeri. Demikian juga, konsumen dengan persepsi kualitas produk dalam negeri yang tinggi kurang cenderung  untuk membeli produk campuran  dalam dan luar negeri.Kata kunci: etnosentrisme, persepsi kualitas produk, perilaku pembelian